Answer:
x = -9
y = 35/7
Explanation:
Given equations :-
-7y - 4x = 1 ....... ( i )
7y - 2x = 53 ........ ( ii )
From ( i )
-7y = 1 + 4x
![y = ( - (1 + 4x))/(7)](https://img.qammunity.org/2020/formulas/mathematics/high-school/atpx2vwiksimine3uvyr0v5j5mkao33fws.png)
..........( iii )
From ( ii )
7y - 2x = 53
7y = 53 + 2x
![y = (53 + 2x)/(7)](https://img.qammunity.org/2020/formulas/mathematics/high-school/6j15w0nbs87ittkkx9t3yw8zl97vaaatn2.png)
.......( iv )
Equating both ( iii ) & ( iv )
y = y
![( - (1 + 4x))/(7) = (53 + 2x)/(7)](https://img.qammunity.org/2020/formulas/mathematics/high-school/7q74klyxojfcpezjegxz0txuizu3p4etll.png)
-(1 + 4x ) = 53 + 2x
-1 -4x = 53 + 2x
-1 - 53 = 2x + 4x
-54 = 6x
-54/6 = x
-9 = x
Also,
![y = ( - (1 + 4x))/(7 ) \\ \\ y = - ((1 + 4( - 9)))/(7)](https://img.qammunity.org/2020/formulas/mathematics/high-school/gfhivqbjde0bdqm5i81l4nf3gafu541fk0.png)
![y = - ( (1 - 36))/(7) \\ \\ y = - (( - 35))/(7) \\ \\ y = (35)/(7)](https://img.qammunity.org/2020/formulas/mathematics/high-school/6k75rliwadqtvwerpbiix4hrsev5xpgfur.png)